José Zorrilla in Mexico: Transatlantic Romanticism and the Question of Artistic Labour. Issue 1 (2nd January 2019) - Seguín, Bécquer
Abstract : This article explores the strategic use of literary form in the Mexican writings of José Zorrilla. The article focuses on México y los mexicanos (1856), a letter Zorrilla wrote to his fellow Spanish Romantic playwright, Ángel de Saavedra, the Duke of Rivas. Zorrilla's México y los mexicanos is a rare piece of epistolary writing in Spanish Romanticism as well as one of the first literary histories of Mexico. Often overlooked in the letter, however, is Zorrilla's economic critique of the precarious condition of artists in both Mexico and Spain. A conservative moderado, Zorrilla could not air his concerns publicly without the threat of retribution from his fellow conservative colleagues in Spain. Zorrilla thus used the epistolary form, the article argues, in order to surreptitiously introduce the economic plight of artists into mainstream Spanish as well as Mexican political discourse. Read in this context, Zorrilla's letter makes visible the fundamental role a transatlantic Romantic vision of labour played in shaping nineteenth-century political discourse in both the Iberian Peninsula and Latin America.